2016
DOI: 10.1002/2015gb005260
|View full text |Cite
|
Sign up to set email alerts
|

Benthic marine calcifiers coexist with CaCO3‐undersaturated seawater worldwide

Abstract: Ocean acidification and decreasing seawater saturation state with respect to calcium carbonate (CaCO 3 ) minerals have raised concerns about the consequences to marine organisms that build CaCO 3 structures. A large proportion of benthic marine calcifiers incorporate Mg 2+ into their skeletons (Mg-calcite), which, in general, reduces mineral stability. The relative vulnerability of some marine calcifiers to ocean acidification appears linked to the relative solubility of their shell or skeletal mineralogy, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 71 publications
(106 reference statements)
1
51
0
Order By: Relevance
“…Laboratory experiments have suggested that ocean acidification will negatively affect calcification in marine organisms, but our understanding of species’ capacity for physiological adjustment is in its infancy. The waters off the western Antarctic Peninsula are naturally undersaturated with respect to the various forms of CaCO 3 (Feely et al., ; Lebrato et al., ). In some areas, the saturation horizon occurs in depths as shallow as ~100 m (Jones et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory experiments have suggested that ocean acidification will negatively affect calcification in marine organisms, but our understanding of species’ capacity for physiological adjustment is in its infancy. The waters off the western Antarctic Peninsula are naturally undersaturated with respect to the various forms of CaCO 3 (Feely et al., ; Lebrato et al., ). In some areas, the saturation horizon occurs in depths as shallow as ~100 m (Jones et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The long‐term ability of marine calcifiers to acclimatize and adapt has not been as thoroughly investigated (Kelly & Hofmann, ), and relatively little research has examined calcification in species that are already living in environments limited in CaCO 3 (but see Hall‐Spencer et al., ; Thomsen et al., ; Thresher, Tilbrook, Fallon, Wilson, & Adkins, ; Shamberger et al., ). Globally, many calcifying species are already exposed to undersaturated seawater, in particular those inhabiting depths >1,200 m (Lebrato et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will have significant consequences, especially for biofouling communities: for example, a decreased proportion of encrusting (Spirorbid) worms and an increase in ascidians and sponges (Peck et al, ). The higher solubility of carbonate at low temperatures means the polar oceans may be particularly affected by undersaturation in the coming decades (Feely, Doney, & Cooley, ; Lebrato et al, ). This contributes to difficulties building external skeletons for taxa such as bivalves, gastropods and echinoderms, which are typically smaller and have thinner shells at high latitudes (McClintock et al, ; Watson et al, ) and for which shell‐building is costly (Watson et al, ).…”
Section: Climate Change Increases the Risk Of Nnms Establishing Arounmentioning
confidence: 99%
“…A wide variety of benthic calcifiers live in waters undersaturated with CaCO 3 , using a range of sophisticated mechanisms for constructing and maintaining their CaCO 3 structures (Lebrato et al 2016).…”
Section: Abiotic Factorsmentioning
confidence: 99%